Homosexuality and Italian cinema : from the fall of Fascism to the years of lead - Giori, Mauro (Palgrave Macmillan, 2020)
This work establishes the relevance of same-sex desires, pleasures and anxieties in the cinema of post-war Italy. It explores cinematic representations of homosexuality and their significance in a wider cultural struggle in Italy involving society, cinema, and sexuality between the 1940s and 1970s